Parameters study on the growth of GaAs nanowires on indium tin oxide by metal-organic chemical vapor deposition - Wu, Dan (2017)
After successful demonstration of GaAs nanowire (NW) epitaxial growth on indium tin oxide (ITO) by metal organic chemical vapor deposition, we systematically investigate the effect of growth parameters' effect on the GaAs NW, including temperature, precursor molar flow rates, growth time, and Au catalyst size. 40 nm induced GaAs NWs are observed with zinc-blende structure. Based on vapor-liquid-solid mechanism, a kinetic model is used to deepen our understanding of the incorporation of growth species and the role of various growth parameters in tuning the GaAs NW growth rate. Thermally activated behavior has been investigated by variation of growth temperature. Activation energies of 40 nm Au catalyst induced NWs are calculated at different trimethylgallium (TMGa) molar flow rates about 65 kJ/mol. The GaAs NWs growth rates increase with TMGa molar flow rates whereas the growth rates are almost independent of growth time. Due to Gibbs-Thomson effect, the GaAs NW growth rates increase with Au nanoparticle size at different temperatures. Critical radius is calculated as 2.14 nm at the growth condition of 430 °C and 1.36 μmol/s TMGa flow rate. It is also proved experimentally that Au nanoparticle below the critical radius such as 2 nm cannot initiate the growth of NWs on ITO. This theoretical and experimental growth parameters investigation enables great controllability over GaAs NWs grown on transparent conductive substrate where the methodology can be expanded to other III–V material NWs and is critical for potential hybrid solar cell application.